2014
DOI: 10.1097/mbc.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the Wells clinical prediction model and ventilation-perfusion scanning for pulmonary embolism diagnosis in pregnancy

Abstract: Pulmonary embolism is one of the leading causes of mortality in pregnancy in the Western world. No clinical prediction models have been validated in pregnancy. As a result, any pregnant woman presenting with signs possibly consistent with pulmonary embolism is investigated radiologically. This study investigates whether using clinical prediction models for pulmonary embolism in pregnancy should be pursued in future prospective trials. The aim of this study was to retrospectively evaluate the Wells clinical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
0
36
0
2
Order By: Relevance
“…O'Connor et al 17 reported that a modified Wells's score of ≥ 6 units (meaning that PE is likely) has a sensitivity of 100% and a specificity of 90% for PE, whereas Cutts et al 8 reported a sensitivity of 100% (95% CI 40% to 100%) and a specificity of 60% (52% to 67%). The wide CIs for sensitivity mean that further research is required.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Connor et al 17 reported that a modified Wells's score of ≥ 6 units (meaning that PE is likely) has a sensitivity of 100% and a specificity of 90% for PE, whereas Cutts et al 8 reported a sensitivity of 100% (95% CI 40% to 100%) and a specificity of 60% (52% to 67%). The wide CIs for sensitivity mean that further research is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We have since updated the literature searches and have identified an additional four papers, along with the published version of the paper in press. 8 These are outlined in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Klinik skorlama yöntemlerinden Wells kriterlerinin gebelikte kullanımıyla ilgili prospektif olarak kullanılmamıştır (9). Yüz seksen üç hastayı içeren retrospektif bir çalışma-da ise modifiye Wells kriterlerinin (PE olası ve PE olası değil) sensitivite ve negatif prediktif değeri %100 olarak bulunmuştur (10).…”
Section: Introductionunclassified
“…O'Connor et al published a retrospective analysis of 125 pregnant women who were referred for CT angiography [107], whereas Cutts et al retrospectively investigated 183 pregnant patients who underwent ventilation perfusion scanning for suspected PE [108]. In both studies, no patients with a Wells score of less than 6 points had confi rmed PE, corresponding to sensitivity and an NPV of 100 % [107,108]. Further prospective evaluation of this clinical prediction model is required.…”
Section: Clinical Pre-test Probabilitymentioning
confidence: 99%
“…Because pregnant women frequently develop leg swelling or dyspnoea unrelated to DVT or PE, and are less likely to have comorbidities included as risk factors in these models, these scores might not be applicable during pregnancy and cannot be recommended [50]. O'Connor et al published a retrospective analysis of 125 pregnant women who were referred for CT angiography [107], whereas Cutts et al retrospectively investigated 183 pregnant patients who underwent ventilation perfusion scanning for suspected PE [108]. In both studies, no patients with a Wells score of less than 6 points had confi rmed PE, corresponding to sensitivity and an NPV of 100 % [107,108].…”
Section: Clinical Pre-test Probabilitymentioning
confidence: 99%